2004
DOI: 10.1128/mcb.24.2.662-674.2004
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of DNA Damage Responses via the Smc5/Smc6 Complex

Abstract: The detection of DNA damage activates DNA repair pathways and checkpoints to allow time for repair. Ultimately, these responses must be coordinated to ensure that cell cycle progression is halted until repair is completed. Several multiprotein complexes containing members of the structural maintenance of chromosomes family of proteins have been described, including the condensin and cohesin complexes, that are critical for chromosomal organization. Here we show that the Smc5/Smc6 (Smc5/6) complex is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
125
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(136 citation statements)
references
References 61 publications
(93 reference statements)
11
125
0
Order By: Relevance
“…The majority of aberrations observed have DNA stretched out along the axis of the mitotic spindle. This phenotype matches well that recently described for the loss of function of two other components of the Smc5ϩ6 complex, Nse1 and Smc6 Harvey et al, 2004). The nse3-1 phenotype could be consistent with a failure to fully condense chromosomes or, a physical impediment to their segregation such as sister chromatid catenation and unresolved recombination structures.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…The majority of aberrations observed have DNA stretched out along the axis of the mitotic spindle. This phenotype matches well that recently described for the loss of function of two other components of the Smc5ϩ6 complex, Nse1 and Smc6 Harvey et al, 2004). The nse3-1 phenotype could be consistent with a failure to fully condense chromosomes or, a physical impediment to their segregation such as sister chromatid catenation and unresolved recombination structures.…”
supporting
confidence: 70%
“…SMC heterodimers need to associate with specific non-SMC family subunits to be functional. Non-SMC subunits of the cohesin, condensin and Smc5ϩ6 complexes have been isolated and characterized (Fujioka et al, 2002;Hirano, 2002;Jessberger, 2003;McDonald et al, 2003;Harvey et al, 2004). Mutants of these non-SMC subunits display phenotypes very similar to those of the SMC mutants, consistent with their interdependent functions.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…SMC protein functions have been strongly implicated in DNA damage responses and DNA repair processes. It has been shown that cohesin, SMC5/SMC6 and Rad50 (another SMC protein) all localize to sites of DSBs, directing homologous recombination DNA repair and inducing S phase checkpoint (Lehmann, 2005;Kim et al, 2002;Yazdi et al, 2002;Kitagawa et al, 2004;Harvey et al, 2004).…”
Section: Screening Candidate Centrosomal Protein Xcep63 Regulates Spmentioning
confidence: 99%